2021
DOI: 10.7759/cureus.19187
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Skull Base Chordoma Presenting As Chordoma Apoplexy

Abstract: Intratumoral hemorrhage/apoplexy in clival chordomas is extremely uncommon, with only 16 reported cases. The average age of patients was 46.2 years and slightly more than half were men. In cases published before 1990, all patients died from their disease without any intervention. Since then, 11 patients have undergone resection by a variety of approaches and there have been no deaths. The diagnosis of skull base chordomas relies on a combination of clinical presentation and radiographic features related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…ntracranIal chordomas are rare tumors that arise from prenatal remnants of the notochord located in the midline skull base clivus. [1][2][3][4] They account for 0.5% of all intracranial tumors and have an incidence of 1 case per million persons. 5,6 Despite initial surgery, chordomas are locally aggressive and have a high rate of local recurrence.…”
mentioning
confidence: 99%
“…ntracranIal chordomas are rare tumors that arise from prenatal remnants of the notochord located in the midline skull base clivus. [1][2][3][4] They account for 0.5% of all intracranial tumors and have an incidence of 1 case per million persons. 5,6 Despite initial surgery, chordomas are locally aggressive and have a high rate of local recurrence.…”
mentioning
confidence: 99%
“…The etiology of chordoma hemorrhage is poorly understood but has been reported in the literature, mainly in clival chordomas [3,6]. Some authors have reported that rapid tumor growth without adequate matched blood supply may cause small friable vessels to rupture, and vascular proliferation and subsequent occlusion of smaller vessels may also cause tumor necrosis and hemorrhage [6]. To our knowledge, this is the first case of sacrococcygeal chordoma with SR due to a reduction in its hemorrhagic component described.…”
Section: Discussionmentioning
confidence: 87%
“…The decrease in size of the hemorrhage occurred as fast as in 4 weeks. The etiology of chordoma hemorrhage is poorly understood but has been reported in the literature, mainly in clival chordomas [3,6]. Some authors have reported that rapid tumor growth without adequate matched blood supply may cause small friable vessels to rupture, and vascular proliferation and subsequent occlusion of smaller vessels may also cause tumor necrosis and hemorrhage [6].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 ) Chordomas exhibit highly variable clinical behavior, ranging from mild to highly aggressive, which complicates their management. 3,5 Gross-total resection (GTR) accompanied by adjuvant radiation therapy represents the current treatment paradigm for most skull base chordomas (SBCs); however, GTR is challenging given their proximity to critical neurovascular structures such as the cranial nerves and major vessels. [6][7][8][9][10][11] Despite an aggressive treatment regimen, the median overall survival (OS) is only 6-7 years.…”
mentioning
confidence: 99%